Exploring Instagram Reels’ Influence on English Learners’ Motivation and British Accent Speaking Skills - Chaerunnissa, Chaerunnissa; Astri, Zul; Imansari, Nurul (Universitas Sulawesi Barat, 2025)
This exploratory qualitative study examines how Instagram Reels content influences English learners' motivation and perceived speaking skill development in British accent acquisition. Conducted between November and December 2023, the research involved semi-structured interviews with two Indonesian followers of Zelina Fahrani, a content creator with over one million followers specializing in British accent pronunciation videos. Data were collected through online interviews via Instagram and WhatsApp, supplemented by systematic observation of Reels content and engagement metrics. Thematic analysis revealed six key themes: digital content as motivational catalyst, spontaneous imitative practice behavior, thematic relevance and personal interest alignment, aesthetic appeal of British accents, enhanced self-efficacy and speaking confidence, and expanded metalinguistic awareness. Both participants reported heightened learning enthusiasm, particularly due to culturally relevant content themes such as Harry Potter references, increased practice frequency, greater confidence in English speaking, and improved awareness of accent variations. However, all findings were self-reported without objective verification, and the small sample size significantly limits generalizability. This preliminary investigation suggests that engaging, theme-based short-form video content on social media platforms may serve as supplementary motivational tools for informal accent learning, warranting further research with larger samples, diverse participant demographics, and objective assessment measures to validate these exploratory findings.